Use and outcomes from neoadjuvant chemotherapy in borderline resectable pancreatic ductal adenocarcinoma in an Australasian population. Issue 1 (13th July 2022) - Walpole, Imogen; Lee, Belinda; Shapiro, Jeremy; Thomson, Benjamin; Lipton, Lara; Ananda, Sumitra; Usatoff, Val; Mclachlan, Sue‐Ann; Knowles, Brett; Fox, Adrian; Wong, Rachel; Cooray, Prasad; et al.
Abstract: Background: Use of neoadjuvant (NA) chemotherapy is recommended when pancreatic ductal adenocarcinoma (PDAC) is borderline resectable Method: A retrospective analysis of consecutive patients with localized PDAC between January 2016 and March 2019 within the Australasian Pancreatic Cancer Registry (PURPLE, Pancreatic cancer: Understanding Routine Practice and Lifting End results) was performed. Clinicopathological characteristics, treatment, and outcome were analyzed. Overall survival (OS) comparison was performed using log‐rank model and Kaplan–Meier analysis. Results: The PURPLE database included 754 cases with localised PDAC, including 148 (20%) cases with borderline resectable pancreatic cancer (BRPC). Of the 148 BRPC patients, 44 (30%) underwent immediate surgery, 80 (54%) received NA chemotherapy, and 24 (16%) were inoperable. The median age of NA therapy patients was 63 years and FOLFIRINOX (53%) was more often used as NA therapy than gemcitabine/nab‐paclitaxel (31%). Patients who received FOLFIRINOX were younger than those who received gemcitabine/nab‐paclitaxel (60 years vs. 67 years, p  = .01). Surgery was performed in 54% (43 of 80) of BRPC patients receiving NA chemotherapy, with 53% (16 of 30) achieving R0 resections. BRPC patients undergoing surgery had a median OS of 30 months, and 38% (9 of 24) achieved R0 resection. NA chemotherapy patients had a median OS of 20 months, improving to 24 months versus 10 months for patients receiving FOLFIRINOX compared to gemcitabine/nab‐paclitaxel (Hazard Ratio (HR) .3, p  < .0001). Conclusions: NA chemotherapy use in BRPC is increasing in Australia. One half of patients receiving NA chemotherapy proceed to curative resection, with 53% achieving R0 resections. Patients receiving Infusional 5‐flurouracil, Irinotecan and Oxaliplatin (FOLIRINOX) had increased survival than gemcitabine/nab‐paclitaxel. Treatment strategies are being explored in the MASTERPLAN and DYNAMIC‐Pancreas trials. Abstract : This study aimed to describe the current practice in Australasia in managing potentially resectable pancreatic cancer. Description of neoadjuvant chemotherapy (NAT), surgical and survival outcomes in borderline resectable pancreatic cancer (BRPC) using real‐world data was extracted from PURPLE (Pancreatic cancer: Understanding Routine Practice and Lifting End results).